Evaluation of Madrasah-Based Management Programs In Private Aliyah Madrasah In Jonggat District, Lombok Central Nusa Tenggara Barat - Suhardi, Muhamad; Mulyadi, Didi; Huda, Syafaat Ariful (International Journal for Educational and Vocational Studies, 2020)
The objective of the research was to understand, explain and improve The Management Program based on Madrasah (Islamic Concept). The research used qualitative approach which used evaluation model of CIPP (Context, Input, Process and Outcome). It was conducted at Islamic State High School Jonggat sub-district. The results are, some weakness of programs to increase teachers human resources that are not master learning model media (cannot operate the laptop and in focus), increasing the facilities need dan low cost. The recommendation is suggested to those who are in the stakeholders to pay attention to this issue. So, the implementation of the program could be done successfully later.